Linagliptin Regulates the Mitochondrial Respiratory Reserve to Alter Platelet Activation and Arterial Thrombosis - Li, Yi; Li, Rong; Feng, Ziqian; Wan, Qin; Wu, Jianbo (Frontiers in Pharmacology, 2020)
Background: The pharmacological inhibition of dipeptidyl peptidase-4 (DPP-4) potentiates incretin action, and DPP-4 is a drug target for type 2 diabetes and reducing cardiovascular risk. However, little is known about the non-enteroendocrine pathways by which DPP-4 might contribute to ischaemic cardiovascular events. Methods: We tested the hypothesis that inhibition of DPP-4 can inhibit platelet activation and arterial thrombosis by preventing platelet mitochondrial dysfunction and release. The effects of pharmacological DPP-4 inhibition on carotid artery thrombosis, platelet aggregation, and platelet mitochondrial respiration signalling pathways were studied in mice. Results: Platelet-dependent arterial thrombosis was significantly delayed in mice treated with high dose of linagliptin, a potent DPP-4 inhibitor, and fed normal chow diet compared to vehicle-treated mice. Thrombin induced DPP-4 expression and activity, and platelets pretreated with linagliptin exhibited reduced thrombin-induced aggregation. Linagliptin blocked phosphodiesterase (PDE) activity and contrained cAMP reduction when thrombin stimulates platelets. Linagliptin increases the inhibition of platelet aggregation by nitric oxide (NO). The bioenergetics profile revealed that platelets pretreated with linagliptin exhibited decreased oxygen consumption rates in response to thrombin. In transmission electron microscopy, platelets pretreated with linagliptin showed markedly reversed morphological changes in thrombin-activated platelets, including the secretion of α-granules and fewer mitochondria. Conclusion: Collectively, these findings identify distinct roles for DPP-4 in platelet function and arterial thrombosis.